The Management of Ureteropelvic Junction Obstruction Presenting with Prenatal Hydronephrosis - C.D. Anthony Herndon; David M. Kitchens (The Scientific World Journal)
The treatment of the newborn diagnosed with a ureteropelvic obstruction prenatally should follow a systematic approach. Although a majority of patients can be followed without surgical intervention, controversy exists concerning appropriate follow-up. Furthermore, a significant number of patients will manifest mild disease and thus deserve abbreviated follow-up. Herein, an appropriate algorithm and a review of the literature are discussed.